Cabo Verde : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Context: Over the last two decades, good governance and sound macroeconomic management have delivered remarkable economic and social progress to Cabo Verde. More recently, however, growth has slowed due to the prolonged downturn in Europe and a sharp deterioration in domestic confidence. A longer-term decline in the contribution of total factor productivity to growth may also have played a role. Financial stability risks have increased with the rise in non-performing loans and fall in bank profitability. The country remains vulnerable to external shocks, given its dependence on tourism, remittances, and concessional financing. Over the longer term, Cabo Verde's challenge as a new middle-income country is to bolster productivity and diversify the sources of growth. Fiscal consolidation remains critical to safeguard macroeconomic and debt sustainability. Budgetary plans for 2014 and the medium term entail rising public debt, and are subject to downside risks to revenue. The authorities have already decided on a package of expenditure containment measures for 2014-17. However, given the high albeit sustainable level of public debt, further measures are needed to put public debt on a more robust downward path. Bolstering domestic revenue mobilization, increasing the efficiency of public investment, and managing existing infrastructure better are also central to sound public finances. International reserves have recovered, which provided room to ease monetary policy in support of the recovery. In the absence of imminent pressures on the balance of payments or on prices, and with private sector credit growth having stalled, the central bank has cut the policy rate. At the same time, given pressures on the banking system, continued vigilance regarding risks to financial stability is warranted. Structural reforms hold the key to bolstering competitiveness, creating jobs, and delivering inclusive growth. Increasing labor market efficiency and reducing skill mismatches would be particularly beneficial in this regard. Enhancing the efficiency of state-owned enterprises is also essential to improve delivery of infrastructure services. Data are adequate for surveillance purposes, though some key shortcomings remain. In particular, national accounts data are released with a long delay. This complicates the formulation of macroeconomic policies.